Feasibility study on hybrid energy harvesting solution in rail transportation system - Khan, Abdul Moeed; Akmurzina, Kalamkas; Bagheri, Mehdi (Frontiers in Energy Research, 2025)
Nowadays, given ecological concerns, including greenhouse gas (GHG) emissions and climate change, it is critical to look into environmentally friendly and sustainable energy sources (SES). This study examines the viability of using photovoltaic (PV) and micro wind turbine (WT) energy systems for hybrid energy (HE) harvesting in rail transportation systems. To meet the energy requirements of Kazakhstan’s railway systems, this study investigates the importance of employing PV, WT, solar sleepers, and a battery energy storage system (BESS). The Talgo Tulpar passenger train traveling from Astana to Almaty has been selected for this study. The integration of solar sleepers over the rail track is also taken into consideration. This article proposes a strategic plan for the system’s operating principles. The methodology involved examining three distinct cases: PV/WT/Grid (Case 1), PV/WT/BESS/Grid (Case 2), and PV/WT/BESS/Grid/Solar sleeper (Case 3). This system was mathematically modeled and simulated using a MATLAB algorithm. The major findings indicate that Case 1 achieves higher energy savings compared to Case 2, while Case 3 results in significantly greater savings than both Case 1 and Case 2. The results suggest considerable cost savings because less grid electricity is needed, which in turn leads to a reduced CO2 footprint.